2015
DOI: 10.3390/ijms160510105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-Cyclodextrin Inclusion Complex on the Absorption of R-α-Lipoic Acid in Rats

Abstract: R-α-lipoic acid (RLA) is an endogenous organic acid, and works as a cofactor for mitochondrial enzymes and as a kind of antioxidant. Inclusion complexes of RLA with α-, β- or γ-cyclodextrins (CD) were prepared and orally administered as a suspension to rats. Among them, RLA/γ-CD showed the highest plasma exposure, and its area under the plasma concentration-time curve (AUC) of RLA was 2.2 times higher than that after oral administration of non-inclusion RLA. On the other hand, the AUC after oral administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
0
19
0
2
Order By: Relevance
“…Gamma CD, widely accepted as food constituent, consists of 8 glucose monomers arranged in the form of a cyclic ring. It has been reported to enhance the bioavailability of hydrophobic ingredients such as coenzyme Q10 [5254]. We recruited CDs for aqueous extraction of bioactives from Ashwagandha leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Gamma CD, widely accepted as food constituent, consists of 8 glucose monomers arranged in the form of a cyclic ring. It has been reported to enhance the bioavailability of hydrophobic ingredients such as coenzyme Q10 [5254]. We recruited CDs for aqueous extraction of bioactives from Ashwagandha leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we examined where the enantioselective absorption occurred in the gastrointestinal tract. We previously reported that RLA was rapidly absorbed from the stomach to some extent [ 41 ]. Based on this, we evaluated the absorption separately from the stomach and small intestine after administration of the racemic mixture to pylorus ligated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of surgery and administration was performed as previously reported [ 41 ]. Briefly, under isoflurane anesthesia, the abdomen was opened, the pylorus was slightly lifted and ligated with cotton thread, and then the incision was closed immediately with suture and an adhesive was applied.…”
Section: Methodsmentioning
confidence: 99%
“…γCD, widely accepted for use in food, pharmaceutical, agricultural and chemical industry constitutes of 8 glucose monomers arranged in the form of a cyclic ring. It has been reported to enhance the bioavailability of hydrophobic ingredients such as coenzyme Q10 42 - 44 .…”
Section: Introductionmentioning
confidence: 99%